Use of a Geographic Information System and lichens to map air pollution in a tropical city: San José, Costa Rica - Neurohr Bustamante, Erich (2013)
There are no studies of air pollution bio-indicators based on Geographic Information Systems (GIS) for Costa Rica. In this study we present the results of a project that analyzed tree trunk lichens as bioindicators of air pollution in 40 urban parks located along the passage of wind through the city of San Jose in 2008 and 2009. The data were processed with GIS and are presented in an easy to understand color coded isoline map. Our results are consistent with the generally accepted view that lichens respond to the movement of air masses, decreasing their cover in the polluted areas. Furthermore, lichen cover matched the concentration of atmospheric nitrogen oxides from a previous study of the same area. Our maps should be incorporated to urban regulatory plans for the city of San José to zone the location of schools, hospitals and other facilities in need of clean air and to inexpensively assess the risk for breast cancer and respiratory diseases in several neighborhoods throughout the city.